«Anna Karénine» travestie ou une mise en abyme transtextuelle. Sur quelques pratiques transtextuelles dans la prose d ’Albert Cohen - Sadkowski, Piotr (Studia Romanica Posnaniensia, 2007)
Transtextuality is the first principle o f Albert Cohen’s writing. The author of this paper is trying to reveal the function on the combination of two aspects of transtextuality (external and internal) in generating multiple interpretations of Cohen’s novels. To illustrate this problem the author presents one of the narrative strategies in Albert Cohen’s prose: “transtextual mise en abyme”, applied to Tolstoy’s novel Anna Karenina. This notion refers to the combined effect of transtextual processes (from implicit mention to allusion to travesty) and mise en abyme. The fiction of Anna Karenina transformed by one of Cohen’s heroes, Mangeclous in the eponym novel and in Les Valeureux, is a travesty. Nevertheless if the reader examines this process in an intratextual perspective, he realizes that this transformation is at the same time, because in the travesty of Tolstoy Cohen’s own text (Belle du Seigneur) is mirrored. Thus Karenina’s story in Mangeclous and Les Valeureux is a prolepsis of the fiction of Belle du Seigneur.